Frequently asked questions in pediatric and adolescent practice (your questions answered) - Parthasarathy, A. (Professor of pediatrics); Borker, Anupama S.; Gupta, Alok (Pediatrician); Dharmapalan, Dhanya (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
Frequently Asked Questions in Pediatric & Adolescent Practice is a comprehensive collection of over 600 FAQs, ranging in topics from newborn to adolescent care, and many sub-specialities including neurology, cardiology, gastroenterology and hepatology, nephrology, urology, haematology, oncology, endocrinology, rheumatology, ophthalmology, otorhinolaryngology and dermatology. Other topics covered include immunisation, infectious diseases and intensive care. The questions and answers are straightforward and clearly formatted, enhanced by 259 images and illustrations, and with recommendations for treatment where relevant. Answers are provided by renowned experts in each field, making this book an excellent source of reference for practising paediatricians and family physicians.